Histamine and histidine decarboxylase in the olfactory system and brain of the common cuttlefish Sepia officinalis (Linnaeus, 1758). Issue 7 (24th November 2019) - Scaros, Alexia T.; Andouche, Aude; Baratte, Sébastien; Croll, Roger P.
Abstract: Cephalopods are radically different from any other invertebrate. Their molluscan heritage, innovative nervous system, and specialized behaviors create a unique blend of characteristics that are sometimes reminiscent of vertebrate features. For example, despite differences in the organization and development of their nervous systems, both vertebrates and cephalopods use many of the same neurotransmitters. One neurotransmitter, histamine (HA), has been well studied in both vertebrates and invertebrates, including molluscs. While HA was previously suggested to be present in the cephalopod central nervous system (CNS), Scaros, Croll, and Baratte only recently described the localization of HA in the olfactory system of the cuttlefish Sepia officinalis . Here, we describe the location of HA using an anti‐HA antibody and a probe for histidine decarboxylase (HDC), a synthetic enzyme for HA. We extended previous descriptions of HA in the olfactory organ, nerve, and lobe, and describe HDC staining in the same regions. We found HDC‐positive cell populations throughout the CNS, including the optic gland and the peduncle, optic, dorso‐lateral, basal, subvertical, frontal, magnocellular, and buccal lobes. The distribution of HA in the olfactory system of S. officinalis is similar to the presence of HA in the chemosensory organs of gastropods but is different than the sensory systems in vertebrates or arthropods. However, HA's widespread abundance throughout the rest of the CNS of Sepia is a similarity shared with gastropods, vertebrates, and arthropods. Its widespread use with differing functions across Animalia provokes questions regarding the evolutionary history and adaptability of HA as a transmitter. Abstract : We describe the location of histamine (HA) using an anti‐HA antibody and a probe for histidine decarboxylase (HDC) in the common cuttlefish, Sepia officinalis . We expand upon previous descriptions of HA in the olfactory organ, nerve, and lobe. HDC‐positive cell populations were found throughout the central nervous system. The distribution of HA in the olfactory system of S. officinalis has implications for the evolution of olfaction across the animal kingdom and the versatility of HA as a neurotransmitter.